Sex-Dependent Performance of the Neutrophil-to-Lymphocyte, Monocyte-to-Lymphocyte, Platelet-to-Lymphocyte and Mean Platelet Volume-to-Platelet Ratios in Discriminating COVID-19 Severity - Fors, Martha; Ballaz, Santiago; Ramírez, Hegira; Mora, Francisco X.; Pulgar-Sánchez, Mary; Chamorro, Kevin; Fernández-Moreira, Esteban (Frontiers in Cardiovascular Medicine, 2022)
Background: The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR) and mean platelet volume-to-platelet ratio (MPR) are combined hematology tests useful for the assessment of COVID-19 severity, but different cut-off values have been reported. Sex can significantly impact immune responses and the course of COVID-19, so these combined hematology tests should be differentiated by gender. Purpose: The aim of this study was to evaluate sex differences in the contribution of the NLR, PLR, MLR and MPR to severity and mortality using a sample of COVID-19 patients infected with SARS-CoV-2 from Quito (Ecuador). Methods: This single center observational cross-sectional study included 3280 subjects with COVID-19 disease admitted in the IESS Hospital from Quito. Subjects over 18 years old having a positive result in the real time reverse transcriptase polymerase chain reaction (RT-PCR) test for SARS-CoV-2. Confirmed COVID-19 cases were categorized as Severe (PaO2 < 60 mmHg) and Non-Severe (PaO2 ≥ 60 mmHg). Area under the curve, sensibility and specificity were calculated for these ratios to identify optimal cut-offs according to gender to predict severity and mortality in COVID-19 subjects. Results: Covid-19 mortality rate among men was double that in women. Severe and non-surviving patients had a higher NLR and MLR, and a lower MPR. A higher PLR was also associated with severity, but not with mortality. The means of NLR, MLR, and PLR in men were significantly higher, yet MPR levels were lower than in women. In men, these ratios had lower cut-offs than in women (NLR: 2.42 vs. 3.31, MLR: 0.24 vs. 0.35 and PLR: 83.9 vs. 151.9). The sensitivity of NLR, MLR and PLR to predict severity was better in men (69%-77%), while their specificity enhanced in women compared to men (70%-76% vs. 23%-48%). Conclusion: High NLR, MLR, PLR and low MPR levels were related to COVID-19 severity with different performance in men and women.